A study of assessing knowledge, attitude and practice of pharmacovigilance among medical students of a South Indian teaching hospital - Dhananjay, Kulkarni; Himasri, Esanakula (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Pharmacovigilance is the science relating to detection, assessment, understanding and prevention of adverse drug reaction. The purpose is to improve patient safety in relation to use of medicines. It is estimated that only 6-10% of adverse drug reactions (ADRs) are reported worldwide. The underreporting of ADR is due to lack of adequate knowledge, attitude and practice among healthcare professionals towards ADR reporting. Health care professional like physicians, pharmacist and nurses have immense responsibility in reporting ADR. Therefore, the objective of this study was to evaluate the knowledge, attitude and practices (KAP) of undergraduate medical students towards pharmacovigilance. Methods: A cross-sectional KAP based questionnaires study was carried out in 100 undergraduate students of Konaseema Institute of Medical Sciences, Amalapuram. The response of KAP questionnaires were analyzed in percentage and tabular form. Results: Nearly 87% participants heard about pharmacovigilance, but only 65% know its need or purpose. 88% people feel that ADR reporting may improve patient safety. Less than half of the students know about Institutional ADR centre. 81% students have seen ADR but only 31% knew about ADR reporting form and surprisingly only 20% have reported ADR. More than 80% feels reporting ADR will increase patient safety. Conclusions: Participants have good knowledge about Pharmacovigilance but lacks in attitude and practice towards reporting ADR. Greater awareness of pharmacovigilance and incorporation of it in medical curriculum will further strengthen pharmacovigilance activity.